Pengaruh Penggunaan Pembayaran Shopeepay Later Terhadap Perilaku Konsumsi Islam Generasi Milenial Di Surabaya - Farah Dilla Wanda Damayanti; Clarashinta Canggih (ITB AAS INDONESIA Surakarta, 2021)
The study aimed to reveal the impact of Shopeepay Later on the Islamic consumption behavior of the millennial generation in Surabaya. The variables independent were convenience, trust, and lifestyle with variable dependent were Islamic consumption behavior. The Islamic consumption behavior measured by three basic principles of Islamic consumption. The research method used quantitative. Research samples calculated using the formula of Lemeshow with the calculation results of 100 respondents. The primary data collected using a questionnaire linkert scales. The data were analyzed by multiple regression analysis using the T test and F test and coefficient of determination test using the SPSS 24.0. the result showed that the convenience and trust have a positive impact on Islamic consumption behavior, in contrast lifestyle has a negative impact on Islamic consumption behavior.